STUDI KELAYAKAN USAHA PEMBESARAN IKAN PATIN DI KELURAHAN MARGOREJO KECAMATAN METRO SELATAN KOTA METRO - Ismalia Afriani (Jurnal WACANA PERTANIAN, 2014)
This research aims to determine the feasibility of enlarging catfishin Sub Margorejo District of South Metro City Metro. This research method of based on collecting data which refer to previous studies and related information from the fish farmer. The methodology used in this study are: primary data and secondary data, using techniques: questionnaires/questionnaire, interview/live interviews with farmers, observation/observation in the study area.  Population is the whole unit or individual in one area  research, in this case all the farmers who carry out fish farming catfish enlarge mentin Sub Margorejo totaled 20 farmers. A whole population of existing member as many as 20 respondents taken as samples by a method entirely hypothetical sensus. Testing conducted using the method of (1) analysis of R/C ratio (2) break event point or break even and (3) SWOT analysis.  The results showed that based analysis of the financial aspect, technical aspect, market aspect, management aspect, legal aspect, institutional aspect, the social aspects of economis and environmental aspects which carried out shows that the bussiness of enlarging catfishin Sub Margorejo District of South Metro feasible to be developed and indevelopedKeywords: feasibility, catfish, SWOT